2007
DOI: 10.1016/j.jtcvs.2006.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of temperatures measured at standard monitoring sites as an index of brain temperature during deep hypothermic cardiopulmonary bypass conducted for thoracic aortic reconstruction

Abstract: Pulmonary artery temperature measurement is recommended to estimate brain temperature during deep hypothermic cardiopulmonary bypass, even if it is conducted with the sternum opened; however, caution needs to be exercised in interpreting its measurements during periods of the cardioplegic solution infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 34 publications
3
37
0
1
Order By: Relevance
“…This may be attributable to selective brain cooling as concluded by Wang et al 10 or may be a delayed response of bladder temperature during rapid temperature changes when compared with other body core temperatures. 23 Regarding treatment effects on blood pressure Koehn et al 13 and Kallmünzer et al 12 reported conflicting data in healthy volunteers. Interestingly, Koehn et al 13 observed an immediate increase of blood pressure on cooling onset followed by a steady increase over a 2-hour time period, whereas the blood pressure increase in our study was also immediate, but transient (Figure 2).…”
Section: March 2013mentioning
confidence: 99%
“…This may be attributable to selective brain cooling as concluded by Wang et al 10 or may be a delayed response of bladder temperature during rapid temperature changes when compared with other body core temperatures. 23 Regarding treatment effects on blood pressure Koehn et al 13 and Kallmünzer et al 12 reported conflicting data in healthy volunteers. Interestingly, Koehn et al 13 observed an immediate increase of blood pressure on cooling onset followed by a steady increase over a 2-hour time period, whereas the blood pressure increase in our study was also immediate, but transient (Figure 2).…”
Section: March 2013mentioning
confidence: 99%
“…Nasopharyngeal and urinary bladder temperatures correlate well with pulmonary artery temperature except during rapid changes [17]. The temperature measured in the bladder does not reflect core temperature accurately in all patients, in fact, in some patients the measured temperature may vary more than measured skin temperature [17]. Less accurate sites include tympanic, rectal, and deep tissue thermometry.…”
Section: Introductionmentioning
confidence: 93%
“…Since the jugular bulb receives the majority of cerebral blood flow, it is thought to correlate to temperature in the cerebral cortex [17]. However, there is no evidence that measuring jugular bulb temperature or intraparenchymal temperature, compared to other measurements of core body temperature, improves outcomes and they are highly invasive monitors.…”
Section: Monitoring Brain Temperaturementioning
confidence: 99%
See 2 more Smart Citations